Correction: A new strategy for the controllable growth of MOF@PBA architectures. Issue 35 (27th August 2019) - Xiao, Xiao; Zhang, Guangxun; Xu, Yuxia; Zhang, Hualin; Guo, Xiaotian; Liu, Yong; Pang, Huan
Abstract : Correction for 'A new strategy for the controllable growth of MOF@PBA architectures' by Xiao Xiao et al., J. Mater. Chem. A, 2019, 7, 17266–17271.